Digital Transformation of Islamic Studies in Indonesian Pesantren: From the Mosque to the Screen - M. Deni Hidayatullah; Abdul Wahid (Al-Marsus : Jurnal Manajemen Pendidikan Islam, 2026)
Advances in digital technology have driven a transformation in the spaces and systems of Islamic studies at Indonesian pesantren. Studies that were previously centered in the langgar—a traditional physical space—have now shifted to digital screens via online platforms. This study aims to analyze the digital transformation of Islamic studies in Indonesian pesantren by highlighting changes in the study spaces, teaching patterns, the scholarly authority of the kiai, and the perceptions of santri toward contemporary digital-based Islamic learning. This study employs a descriptive-qualitative approach using a literature review method, integratively combined with cyber observation or netnography, at three Islamic boarding schools in Indonesia. The results indicate that digitization has shaped a hybrid scholarly space that integrates traditional pedagogical methods with modern technology. However, this transformation also presents challenges in the form of varying technical infrastructure capacities, as well as the need to negotiate the kiai’s scholarly authority and the students’ etiquette (adab) in virtual spaces. Therefore, digital transformation in Islamic boarding schools requires a balance between the utilization of public technology and the strengthening of autonomous internal scholarly structures.